2017
DOI: 10.1186/s13049-017-0411-z
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical landmarks for safely implementing resuscitative balloon occlusion of the aorta (REBOA) in zone 1 without fluoroscopy

Abstract: BackgroundResuscitative balloon occlusion of the aorta (REBOA) can maintain hemodynamic stability during hemorrhagic shock after a following torso injury, although inappropriate balloon placement may induce brain or visceral organ ischemia. External anatomical landmarks [the suprasternal notch (SSN) and xiphoid process (Xi)] are empirically used to implement REBOA in zone 1. We aimed to confirm if these landmarks were useful for determining a balloon catheter length for safe implementation of REBOA in zone 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 7 publications
2
20
0
Order By: Relevance
“…When fluoroscopy is not available, as in out-of-hospital REBOA or other resource-limited settings, devices with external length marks on the catheter shaft enable correct positioning of the balloon without imaging. Placement depths can be estimated before insertion of the catheter using anatomical landmarks such as the suprasternal notch, mid-sternum, xiphoid process or umbilicus [20,21]. The ER-REBOA™ facilitates accurate positioning with a length mark every cm and the exact length indicated with numbers every 5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…When fluoroscopy is not available, as in out-of-hospital REBOA or other resource-limited settings, devices with external length marks on the catheter shaft enable correct positioning of the balloon without imaging. Placement depths can be estimated before insertion of the catheter using anatomical landmarks such as the suprasternal notch, mid-sternum, xiphoid process or umbilicus [20,21]. The ER-REBOA™ facilitates accurate positioning with a length mark every cm and the exact length indicated with numbers every 5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…If the xed catheters continued to be applied in zone III at this time, it may cause long-term ischemic necrosis of vital organs. Inaba and Okada proposed that sternum was likely to be used to guide the catheter length positioning in zone I [9,10], yet there is no further study on the relevant anatomical structure of zone III.…”
Section: Discussionmentioning
confidence: 99%
“…Inaba et al found that the midpoint of the sternum could be used to guide the correct placement of REBOA in zone I via the study of cadavers [9]. Then, Okada et al showed that the safe catheter length positioning in zone I should be between the distance from the femoral artery to suprasternal notch and that to the xiphoid process [10]. In comparison, the current literatures provide less guidance on good practice in regard to the placement of REBOA in zone III by external landmark.…”
Section: Introductionmentioning
confidence: 99%
“…The approximate insertion depth for positioning the balloon in the desired zone should be estimated beforehand on the basis of anatomical landmarks [37][38][39][40]:…”
Section: Key Pointsmentioning
confidence: 99%